Organizational strategies to reduce physician burnout: a systematic review and meta-analysis - De Simone, Stefania; Vargas, Maria; Servillo, Giuseppe (Aging clinical and experimental research, 2021)
Background The growing “process” of burnout impair performance and quality of professional services, with consequences for physicians, healthcare care organization, and patient’s outcomes. Aims We aim to evaluate which strategy of intervention, individual or organization directed, is more effective to reduce physician burnout and to provide management suggestions in terms of actual organizational strategies and intensity leading to reductions in physician burnout. Methods The meta analysis was conducted according to the PRISMA guidelines. We included physicians of any specialty in the primary, secondary, or intensive care setting, including residents and fellows. Eligible interventions were any intervention designed to relieve stress and/or improve the performance of physicians and reported burnout outcomes, including physician-directed interventions and organization-directed interventions. The electronic search strategy applied standard filters for identification of the different studies. Databases searched were the Cochrane Central Register of Controlled Trials (CENTRAL, The Cochrane Library), MEDLINE (from inception to September 2018), and EMBASE (from beginning to September 2018). Meta analysis was performed with mixed random effect using DerSimonian and Laird method. The standardized mean difference (SMD) and 95% CI for each outcome were separately calculated for each trial pooling data when needed, according to an intention-to-treat principle. Results Pooled interventions were associated with small significant reductions in burnout (SMD = − 0.289; 95% CI, − 0.419 to − 0.159; I2 = 29%) (Fig. 2 ). Organization-directed interventions were associated with a medium reduction in burnout score (SMD = − 0.446; 95% CI, − 0.619 to − 0.274; I2 = 8%) while physician-directed interventions were associated with a moderate reduction in burnout score (SMD = − 0.178; 95% CI, − 0.322 to − 0.035; I2 = 11%). Discussion This systematic review and meta-analysis showed that (1) organization-directed interventions were associated with moderate reduction in burnout score, (2) physician-directed interventions were associated with small reduction in burnout score, (3) organization-directed interventions reduced more the depersonalization than physician-directed interventions, (4) organization-directed interventions were related to a more improvement of the personal accomplishment than physician-directed interventions. Conclusions This meta analysis found that physicians could gain important benefits from interventions to reduce burnout, especially from organizational strategies, by viewing burnout rooted in issues related to the working environment and organizational culture.